THE USE OF PRACTICAL LEARNING ACTIVITIES THAT AFFECT LEARNING ACHIEVEMENT IN PRINT MEDIA PRODUCTION FOR STUDENTS IN COMMUNICATION ART 3rd GRADE, FACULTY OF MANAGEMENT SCIENCE - โฆษิตพิพัฒน์, อรอนงค์ (Academic Journal Phranakhon Rajabhat University, 2019)
The purpose this research was to enhance student learning achievement in using new practical learning activities in Print Media Production Course, to compare learning outcomes pretest and posttest using practical learning activities and to study the students’ satisfaction towards practical learning activities. A one-group pretest and posttest experimental design was conducted. Thirty-three of 3rd year students of Education Faculty, Phranakhon Rajabhat University, who enrolled Print Media Production Course, were participated during the second semester of academic year 2017. The research tools consisted of practical lesson plan in Print Media Production Course, achievement test, and questionnaire. The collected data were analyzed by percentage, mean, standard deviation and t-test for dependent samples. The findings were as follows; the achievement of the practical learning activities was 93.99%, the students’ achievement average scores before practical learning activities were 34.67 but the average scores after practical learning activities were 55.42, which was higher than those before learning with this method at the .05 significances level. The majority of students were satisfied with this practical learning step by step activities at average of 4.19. Most of students had better results from this learning method